2012
DOI: 10.2971/jeos.2012.12001
|View full text |Cite
|
Sign up to set email alerts
|

Unresonant interaction of laser beams with microdroplets

Abstract: The interaction of distilled water droplets (volumes of 3-4 µl) with pulsed laser beams emitted at 532 nm is described. At 532 nm the distilled water absorption is very low and the interaction of a water droplet with the laser radiation is dominated by unresonant phenomena. In this case, following the collision of the laser beam with a droplet in suspended position in air, its deformations and mechanical vibrations are produced. The conditions in which the droplets lose material as a consequence of the impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…These two energies were selected in order to evaluate the effect of laser radiation on droplet's content and they were the limits in terms of beam energy within which modifications of the shape of the droplet took not place. 25 The laser beam was processed so that it could cover the entire droplet and therefore excite a maximum number of dye molecules within it. The fluorescence signal was collected with a VIS optical fiber mounted at 90 with respect to the incident laser beam (along the observation direction in Figure 4(c)) and analyzed with a spectrograph Spectra Pro 750 (Acton Research) coupled with an IMAX 1024 iCCD camera (Princeton Instruments).…”
Section: -4mentioning
confidence: 99%
“…These two energies were selected in order to evaluate the effect of laser radiation on droplet's content and they were the limits in terms of beam energy within which modifications of the shape of the droplet took not place. 25 The laser beam was processed so that it could cover the entire droplet and therefore excite a maximum number of dye molecules within it. The fluorescence signal was collected with a VIS optical fiber mounted at 90 with respect to the incident laser beam (along the observation direction in Figure 4(c)) and analyzed with a spectrograph Spectra Pro 750 (Acton Research) coupled with an IMAX 1024 iCCD camera (Princeton Instruments).…”
Section: -4mentioning
confidence: 99%
“…For each concentration, applied on the droplet was the maximum beam energy which did not distort the droplet shape. Above this energy, unresonant interaction effects (generated by light pressure) [19] took place and produced vibrations or even droplet destruction. In addition, by inducing small vibrations in the droplet, the spherical shape is distorted and the collected signal can be unpredictably altered.…”
Section: Resultsmentioning
confidence: 99%
“…The beam waist in the interaction plane had the linear dimension around the droplet's diameter (1.24 mm). Since the laser beam is not focused on the droplet, one may use a higher beam energy which does not destroy it, so that in total, a more intense fluorescence emission is produced [14,18,19,22].…”
Section: Methodsmentioning
confidence: 99%
“…The interaction of distilled water droplet (3-4 µl volume) with a pulsed laser beam at 532 nm was investigated; the water absorption is very low and the interaction of an aqueous droplet suspended in air with the laser beam is dominated by non-resonant phenomena so that one produces droplet deformations and mechanical vibrations [7,8]. It was shown that the droplets lost material as a consequence of the impact with a laser beam.…”
Section: Laser Beam Non-resonant and Resonant Interaction With Singlementioning
confidence: 99%